GSK-3β as a target for protection against transient cerebral ischemia - Wang, Wei (Int J Med Sci, 2017)
Stroke remains the leading cause of death and disability worldwide. This fact highlights the need to search for potential drug targets that can reduce stroke-related brain damage. We showed recently that a glycogen synthase kinase-3β (GSK-3β) inhibitor attenuates tissue plasminogen activator-induced hemorrhagic transformation after permanent focal cerebral ischemia. Here, we examined whether GSK-3β inhibition mitigates early ischemia-reperfusion stroke injury and investigated its potential mechanism of action. We used the rat middle cerebral artery occlusion (MCAO) model to mimic transient cerebral ischemia. At 3.5 h after MCAO, cerebral blood flow was restored, and rats were administered DMSO (vehicle, 1% in saline) or GSK-3β inhibitor TWS119 (30 mg/kg) by intraperitoneal injection. Animals were sacrificed 24 h after MCAO. TWS119 treatment reduced neurologic deficits, brain edema, infarct volume, and blood-brain barrier permeability compared with those in the vehicle group. TWS119 treatment also increased the protein expression of β-catenin and zonula occludens-1 but decreased β-catenin phosphorylation while suppressing the expression of GSK-3β. These results indicate that GSK-3β inhibition protects the blood-brain barrier and attenuates early ischemia-reperfusion stroke injury. This protection may be related to early activation of the Wnt/β-catenin signaling pathway.